Research of resistant plasticity in national security mechanism - Чернявська, Тетяна Анатоліївна (Technology audit and production reserves, 2016)
Role and resistant properties importance of socio-economic system in the mechanism of national security was justified in the article. Systemic, synergetic, complex, evolutionary and scientific approaches were used to reach the goal and solve the problem. The phenomenon of resistance was revealed by the author as «genetic» property of the system, as a continuous function of it, as a mechanism to secure development. Dialectical relationship between self-sufficiency-resistant securities of socioeconomic system was highlighted in the paper. In addition, the author emphasizes importance of the resistant plasticity determining. Definition of the term is proposed, potential of plasticity of resistant individual components of the socio-economic system is characterized in the article. High level of resistant plasticity of transportation and communication systems is noted in particular. Instrumental quality of transport and communication system in self-preservation from the damaging effects of instability and ensuring national security development is substantiated. Conducted systematic and comprehensive research will lead to the complete understanding of national strategy future development.